THE ROLE OF NATIONAL VALUES IN RAISING CHILDREN IN THE SPIRIT OF PATRIOTISM IN THE FAMILY - Xasonboyev Bekzodjon Valijonovich (American Journals Publishing, 2025)
Today, on the basis of all educational work related to the upbringing of children in the family and mahalla system, experts are obliged to study the laws related to the fundamental essence of folk traditions, in particular, national values preserved in family relations, to study the socio-psychological conditions and to apply the results in practice. Today, the formation of children's beliefs in such values through an influential social institution like the family and through this formation of positive social relations towards the family is one of the urgent issues. In multinational Uzbekistan, which has pursued such a goal, thinking about the future of young people, the role of young people in the development of a civil society and the formation of a new worldview in them is one of the urgent issues of today.